2019
DOI: 10.1017/s1743921319010019
|View full text |Cite
|
Sign up to set email alerts
|

Sun-as-a-star observations of the 2017 August 21 solar eclipse

Abstract: The Potsdam Echelle Polarimetric and Spectroscopic Instrument (PEPSI) is a state-of-the-art, thermally stabilized, fiber-fed, high-resolution spectrograph for the Large Binocular Telescope (LBT) at Mt. Graham, Arizona. During daytime the instrument is fed with sunlight from the 10-millimeter aperture, fully automated, binocular Solar Disk-Integrated (SDI) telescope. The observed Sun-as-a-star spectra contain a multitude of photospheric and chromospheric spectral lines in the wavelength ranges 4200–4800 Å and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The SOLIS/ISS observations started in 2006 December and comprise a much longer period than the PEPSI/SDI data. Dineva, Denker, Verma, et al (2020) demonstrated that the core of the Ca ii K-line obtained with PEPSI/SDI is deeper compared to SOLIS/ISS for the same day. This difference in depth affects the intensity-based parameters.…”
Section: Ca II K-line Parametersmentioning
confidence: 83%
“…The SOLIS/ISS observations started in 2006 December and comprise a much longer period than the PEPSI/SDI data. Dineva, Denker, Verma, et al (2020) demonstrated that the core of the Ca ii K-line obtained with PEPSI/SDI is deeper compared to SOLIS/ISS for the same day. This difference in depth affects the intensity-based parameters.…”
Section: Ca II K-line Parametersmentioning
confidence: 83%
“…The SOLIS/ISS observations started in 2006 December and comprise a much longer period than the PEPSI/SDI data. Dineva et al (2020b) demonstrated that the core of the Ca ii K‐line obtained with PEPSI/SDI is deeper compared to SOLIS/ISS for the same day. This difference in depth affects the intensity‐based parameters.…”
Section: Spectral Indicesmentioning
confidence: 99%